Patient Perspectives on Hypertension Treatment - Janning, Anne Swanson (My University, 2011)
Hypertension affects millions of people in the United States. Some patients do not realize the importance of following their prescribed hypertension treatment. Many do not realize they have hypertension, so when started on medication they do not feel any different, even when their hypertension is controlled. They may feel worse from the side effects of their medications, such as increased tiredness. Since many do not feel symptoms, it can be difficult to understand why a person needs to be on hypertension medication, unless they understand the long term effects uncontrolled hypertension have on the body. The purpose of this study is to gain insight into patients' perspectives on their hypertension treatment. This study will help providers understand what patients feel and what they understand about their treatment. Providers will then have a better understanding of patient needs with their hypertension treatment and where the provider may need to provide more education to the patient. The research study is a descriptive qualitative study. The participants were selected by snowball sampling and were interviewed once by the researcher. Interviews continued until data saturation was achieved. This research provides valuable information for providers who treat patients with hypertension.
A Clinical Paper Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing - Family Nurse Practitioner
Keywords: Hypertension; Hypertension - Patients attitudes